ATF2-driven osteogenic activity of enoxaparin sodium-loaded polymethylmethacrylate bone cement in femoral defect regeneration - Luobin Ding; Kangning Hao; Linchao Sang; Xiaoyu Shen; Ce Zhang; Dehao Fu; Xiangbei Qi (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background Polymethylmethacrylate (PMMA) bone cement loaded with enoxaparin sodium (PMMA@ES) has been increasingly highlighted to affect the bone repair of bone defects, but the molecular mechanisms remain unclear. We addressed this issue by identifying possible molecular mechanisms of PMMA@ES involved in femoral defect regeneration based on bioinformatics analysis and network pharmacology analysis. Methods The upregulated genes affecting the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) were selected through bioinformatics analysis, followed by intersection with the genes of ES-induced differentiation of BMSCs identified by network pharmacology analysis. PMMA@ES was constructed. Rat primary BMSCs were isolated and cultured in vitro in the proliferation medium (PM) and osteogenic medium (OM) to measure alkaline phosphatase (ALP) activity, mineralization of the extracellular matrix, and the expression of RUNX2 and OCN using gain- or loss-of-function experiments. A rat femoral bone defect model was constructed to detect the new bone formation in rats. Results ATF2 may be a key gene in differentiating BMSCs into osteoblasts. In vitro cell assays showed that PMMA@ES promoted the osteogenic differentiation of BMSCs by increasing ALP activity, extracellular matrix mineralization, and RUNX2 and OCN expression in PM and OM. In addition, ATF2 activated the transcription of miR-335-5p to target ERK1/2 and downregulate the expression of ERK1/2. PMMA@ES induced femoral defect regeneration and the repair of femoral defects in rats by regulating the ATF2/miR-335-5p/ERK1/2 axis. Conclusion The evidence provided by our study highlighted the ATF2-mediated mechanism of PMMA@ES in the facilitation of the osteogenic differentiation of BMSCs and femoral defect regeneration.